An Examination of Patient Satisfaction with Spinal Anesthesia Interventions at DIK PUSDIKKES Hospital in East Jakarta - Tarsono, Tarsono; Susanto, Amin; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2024)
Background: Anesthesiology and intensive therapy services in hospitals are one part of the fast-growing health services. High patient satisfaction is one of the hospital's goals. The hospital as a full health care institution must be able to provide excellent service. Purpose: The study aims to determine the level of patient satisfaction with spinal anesthesia at the East Jakarta Pusdikkes Hospital. Methods: The design of this study is descriptive cross sectional, determining the number of samples using the Total Sampling method for as many as 30 respondents. The research instrument used the Evan Lr questionnaire. Findings: The results of the study, as many as 17 (53.1) respondents in post-spinal patients stated that they were satisfied, in patient satisfaction based on age most were aged 26-35 years with a fairly satisfied satisfaction level of 9 respondents (30.0%), at the level of patient satisfaction based on gender in this study most were female with a fairly satisfied satisfaction level of 13 respondents (43.3%), based on the level of education in this study most were high school with a fairly satisfied satisfaction level of 10 respondents (33.3%). Conclusion: From the results of the study, it was concluded that the description of the level of satisfaction with spinal anesthesia at the East Jakarta Pusdikkes Hospital was mostly satisfied.